Constructing surface vacancy to activate the stuck MXenes for high-performance CO2 reduction reaction. (August 2022) - Cao, Shoufu; Hu, Yuying; Yang, Chunyu; Li, Jiao; Chen, Hongyu; Wei, Shuxian; Liu, Siyuan; Wang, Zhaojie; Sun, Daofeng; Lu, Xiaoqing
Abstract: Due to the superior metallic conductivity, enhanced hydrophilic property, and large surface area, MXene has become a well-acknowledged revolutionary 2D material and may exhibit great potentials in CO2 reduction reaction (CO2 RR). Herein, Mo2 C, Mo2 CO2, single O vacancy Mo2 CO2 (Mo2 CO2 -Ov1 ), and adjacent two O vacancy Mo2 CO2 (/Mo2 CO2 -Ov2 ) were employed as probes to explore the vacancy effect of surface termination on MXenes towards the catalytic performances for CO2 RR. Results showed that O vacancies were readily formed on Mo2 CO2, leading to the formation of O-vacancy Mo2 CO2 which possessed fair thermodynamic stability and preserved the electronic feature of Mo2 C near Fermi level. The exposed d z 2, dxz, and dyz orbitals of Mo around 1.70 eV benefited to CO2 stabilization and activation. Mo2 CO2 -Ov1 exhibited considerable activity toward CH4 and CO, while Mo2 CO2 -Ov2 performed superior activity and selectivity toward CH4 at a low applied potential of − 0.31 V, surpassing most MXenes and Cu catalysts. The stuck Mo2 CO2 could thus be effectively activated for high-performance CO2 RR via surface O vacancy construction. This work discovered MXene materials as potential CO2 RR catalysts and highlighted the significant promotion effect by constructing surface vacancy on MXene catalytic performances. Graphical Abstract: By virtue of O vacancy effect, the stuck Mo2 CO2 is activated as promising CO2 RR catalyst. Mo2 CO2 -Ov1 exhibits limiting potential of − 0.34 V for CO and CH4 production. Mo2 CO2 -Ov2 can effectively produce high-purity CH4 form CO2 RR at low limiting potential of − 0.31 V. A simple O vacancy treatment can activate MXenes as superior CO2 RR catalysts. ga1 Highlights: ● Constructing O vacancy can effectively activate stuck MXenes for superior CO2 RR. ● O-vacancy Mo2 CO2 inherits the activity of Mo2 C and stability of Mo2 CO2 . ● Single O vacancy Mo2 CO2 exhibits considerable activity toward CH4 and CO. ● Adjacent two O vacancy Mo2 CO2 performs superior activity and selectivity toward CH4 .